Synthesis and characterization of the radiopharmaceutical [18F]fluoroestradiol (Brazilian Journal of Radiation Sciences, 2021)
[18F]Fluoroestradiol ([18F]FES), an estrogen analog, may be used in Positron Emission Tomography (PET) for evaluation of the tumor cell receptor profile in a noninvasive way, which is an important factor for determining the therapy to be used, disease staging, prognosis and response to therapy in breast cancer. [18F]FES is a new radiopharmaceutical and does not have an official monograph in any pharmacopeia until now. Therefore, the objective of this work was the optimization of the [18F]FES automatic synthesis and the elaboration of an analytical protocol for final product analyses. Initially, the synthesis of [18F]FES was performed according to a modified commercial protocol, using a TracerLab MXFDG synthesis module specific for [18F]FES synthesis. New protocols for the physicochemical quality control assays of the radiopharmaceutical were developed, including pH, chemical purity, residual solvents, radiochemical identity and purity. Physicochemical and microbiological analysis were performed with the synthesized [18F]FES at different time points to evaluate its stability. The uncorrected synthesis yield was 18.37 ± 3.07 %. All Quality Control methodologies proved to be effective for the product. The physicochemical and microbiological results obtained in the stability study showed that [18F]FES is stable during 8 hours after its synthesis, even under stress conditions. At the end of the study, it was concluded that the [18F]FES complies with all specifications required for a radiopharmaceutical intended for diagnostic use.